The application of predictive analysis in the management of investment project portfolios - Wach, Maciej (Zastosowanie analizy predykcyjnej w zarządzaniu portfelami projektów inwestycyjnych, 2021)
The purpose of this paper is to indicate the possibilities of applying predictive analytics in the area of investment project portfolio management. In the article, deductive reasoning, critical analysis of the literature and the analysis of selected decision cases were used as the research method. The author presents the process of the investment project portfolio management. The decision-making problems are highlighted, along with the consequences that poor portfolio management may have on the enterprise. Predictive analytics is characterised as a tool for aiding decision-makers together with basic requirements for its application in any organization. As a result, a framework is presented, which uses new approach, where project is considered as a parametrised object that follows patterns created by past cases. Predictive algorithms are suggested for specific decision-making problems met by portfolio managers. The author also discusses the limitations of the proposed solutions.
Informatyka Ekonomiczna = Business Informatics, 2021, Nr 4 (62), s. 51-61
Keywords: predictive analysis; investment project; portfolio management; analiza produkcyjna; zarządzanie projektami; portfele inwestycyjne